2-(4,5-Dihydro-1H-imidazol-2-yl)pyridine - Reza Kia; Hoong-Kun Fun; Hadi Kargar (Acta Crystallographica Section E, 2009)
In the molecule of the title compound, C8H9N3, a new imidazoline derivative, the six- and five-membered rings are slightly twisted away from each other, forming a dihedral angle of 7.96 (15)°. In the crystal structure, neighbouring molecules are linked together by intermolecular N—H...N hydrogen bonds into extended one-dimensional chains along the a axis. The pyridine N atom is in close proximity to a carbon-bound H atom of the imidazoline ring, with an H...N distance of 2.70 Å, which is slightly shorter than the sum of the van der Waals radii of these atoms (2.75 Å). The crystal structure is further stabilized by intermolecular C—H...π and π–π interactions (centroid-to-centroid distance 3.853 Å).